LAYANAN KONSELING ISLAMI DALAM MENANGGULANGI STRES BELAJAR SISWA KELAS XI SMA NEGERI 1 SELESAI - Frastika Agtha (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2021)
The problem in this study is Islamic Counseling Services in Overcoming Learning Stress for Class XI Students of SMA Negeri 1 Completed the 2018/2019 Academic Year. This study aims to determine student learning stress inside or outside the classroom, Islamic counseling conducted by BK teachers in schools, Islamic counseling services in dealing with learning stress for class XI students.Â Methodologically, this research is a phenomenological qualitative research. The method used in data collection is observation, interviews and documentation. To analyze the data, the researcher uses qualitative analysis with the steps of data exposure, data reduction and drawing conclusions.Â The general finding in this study is the objective condition of class XI SMA Negeri 1 Completed. The results of the research are: (1) . The learning stress of class XI SMA Negeri 1 students has been resolved, (2) Islamic Counseling Services in Overcoming Study Stress for Class XI Students at SMA Negeri 1 Completed and running smoothly, (3) Specifications for dealing with learning stress for class XI students in SMA Negeri 1 Completed has been overcome , (4) The supporting factors and inhibiting factors in overcoming the learning stress of class XI students at SMA Negeri 1 Finish have been overcome.